Potential Anti-Coronavirus Agents and the Pharmacologic Mechanisms - Yang Y; Cui X; Wei H; Guo C; Zhang Y (Dove Medical Press, 2021)
Yang Yang,1,* Xiao Cui,1,* Huaying Wei,1 Caiping Guo,1 Yulin Zhang2 1Department of Infectious Diseases, Beijing You an Hospital, Capital Medical University, Beijing Institute of Hepatology, Beijing, 100069, People’s Republic of China; 2Department of Respiratory and Infectious Diseases, Beijing You an Hospital, Capital Medical University, Beijing Institute of Hepatology, Beijing, 100069, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yulin ZhangDepartment of Respiratory and Infectious Diseases, Beijing You an Hospital, Capital Medical University, Beijing Institute of Hepatology, Beijing, 100069, People’s Republic of ChinaTel +86 10-83997143Fax +86 10-63293371Email yulinzhang@ccmu.edu.cnAbstract: Severe acute respiratory syndrome coronavirus clade 2 (SARS-CoV-2) is an emerging pathogen, which is similar to previous SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV) occurrences. However, we only get few understandings about the pathogenesis of SARS-CoV-2, which need to further be studied. The discovery of an agent that has a treatment efficacy against SARS-CoV-2 is very urgent. In this review, we briefly discuss the virology of this pathogen and focus on the available understanding of the pathogenesis and treatments of this pathogen including the uses of nucleoside analogues, protease inhibitors, interferons, and other small-molecule drugs, on the basis previous comprehensions of SARS and MERS. These reviewed concepts may be beneficial in providing new insights and potential treatments for COVID-19.Keywords: COVID-19, SARS, MERS, virology, pathogenesis, treatment